Name-strategies and antropoiesis discourse in the history of philosophy - S. G. Selivanova (Концепт: философия, религия, культура, 2020)
Onomapoiesis strategies actualize the distinctive sphere of human practice, which is a direct continuation of autopoiesis and anthropoiesis. They atomize and ontologize the Self by restricting it to definite structure-morphologic clusters of language expressions, such as personal name and pronoun. As a result, we have two completely different tactics: naming tactics and pronoun tactics, or ego-strategies. These practices refer to diverse complexes and can’t be considered within one species, each of them constitutes the autonomous entity. Any self-naming, self-calling, and indication through the name or pronoun, correlates with the innate eager and desire of a person to express himself, the world, and other(s). Thus, the anthropology of naming turns out to be the part of philosophical discourse, implicitly passing through the entire history of thought. Primarily, the philosophy of Stoics belongs to this kind of boundary marks, within the framework of which the distinction between the name and the pronoun was made for the first time. Plus, the discovery of deixis belongs to them. In the context of the modern era of philosophy, the doctrine of Rene Descartes is a kind of counterpoint when the Self, the Ego, first reveals itself to consciousness. Further, there is a fission inside the indicated complexes: I and not-I, My and not-My, I and You, We and They, I and the Other, I and Others manifest themselves inside the pronoun practices of naming. Their contents and meanings become the subject of philosophy and linguistic, as well as interdisciplinary studies. There are two conceptually framed strategies within one complex, which illustrates the praxeological character of the study: the Heideggerian Dasein and the polyphonic Ego presented by Bakhtin M.M. The first one unfolds as a monologue and first-person speech; the latter in turn, as a dialog, which expresses the subject’s being as a complicity in the polyphony of voices of the Other(s).